Tahapan Kematangan Manusia: Analisis Karakteristik Perkembangan Remaja dan Dewasa Dalam Perspektif Psikologi - Juwita, Ajeng Intan; Sagita, Eva (Addabani: Interdisciplinary Journal of Islamic Education, 2025)
This study analyzes the stages of human maturity, focusing on adolescent and adult development from a psychological perspective. The maturational process is a complex journey involving physical, cognitive, emotional, and social changes. Adolescence is characterized by the search for identity and emotional instability, while adulthood reflects personality stability and social responsibility. This study explores the differences between psychological and biological maturity and the factors influencing them. The method used is a descriptive qualitative approach through a literature review that analyzes theories and empirical findings in human development. The results indicate that psychological maturity does not always align with biological maturity; environmental factors, culture, and individual experiences significantly influence personality characteristics. These findings provide deeper insights into the dynamics of human development that can be applied in education, counseling, and psychological interventions. Recommendations include developing educational programs that address individual differences in psychological maturity to support optimal development.